(untitled) (Bangladesh Journal of Child Health, 2021)
Background: Colonoscopy of the lower gastrointestinal tract has both diagnostic and therapeutic value. Objective: This cross-sectional study aimed to investigate the indications, findings and complications of children who underwent the colonoscopy. Materials & Methods: We studied the children between 1 and 18 years of age who presented with various indications and underwent both diagnostic and therapeutic colonoscopy in the Department of PGN, BSMMU, Dhaka from January 2015 to February 2018. Results: Among the total 332 patients reviewed,61.7% (205) were male and 38.3% (127)with a male to female ratio of 1.61:1. The most common (69.8%) indication was lower gastrointestinal bleeding (LGIB) followed by diarrhea (15.9%) and altered bowel (14%) as well. No serious complications occurred during the procedures. A total of 211 patients (63.5%) received a diagnosis, including 137 (41.3%) patients with colorectal polyps, erythema 40(12%) and diffuse nonspecific colitis 34(10.2%).Ninety four percent polyps are located in recto-sigmoid region. Juvenile polyp was the most common pathological findings. Conclusion: LGIB is the commonest indication for pediatric colonoscopy. Pediatric colonoscopy is effective diagnostic as well as therapeutic option for lower GI pathology. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 25-28